Zarys problematyki offsetu w kontekście rozwoju polskiego przemysłu obronnego - Machniak, Arkadiusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article describes a phenomenon of offset in a general outline. Offset is a new concept in the Polish arms industry. This phenomenon has many supporters and critics, as well as being a tool in the hands if lobbyists. It is also assessed through the prism of political events. It has played an important role in the Polish defense industry in recent years. As a result, the access to new technologies and markets has been greater. Offset has a significant importance on the macroeconomic view but it is not the only way of developing the Polish defense industry.
An outline of the issues of offset in the context of the development of the polish defense industry
Keywords: defense industry; development; technology; commitment